Effect of temporal and spatial variability on the classification of the Ecological Quality Status using the CARLIT Index. Issue 1 (15th January 2016) - Cavallo, Marianna; Torras, Xavier; Mascaró, Oriol; Ballesteros, Enric
Abstract: Methodologies developed by European Member States to assess the environmental quality of their coastal waters under the EU Water Framework Directive (WFD, 2000/60/EC) may have an associated source of uncertainty. Here we identify and quantify the level of uncertainty in the CARLIT (Cartography of littoral and upper-sublittoral communities) methodology to test its effectiveness and reliability. The outcomes show that the effect of temporal variability (among years) within each water body is low when CARLIT is performed every year along the entire rocky coast. The spatial variability within a water body is also low. According to these results, CARLIT could be performed every 3 years across all the water body or, alternatively, every year considering at least 60% of each water body, without a significant reduction of the confidence in the classification of the Ecological Quality Status (EQS). Highlights: Temporal and spatial variability of CARLIT is low. The monitoring with CARLIT can be performed every three years without losing accuracy. The monitoring with CARLIT can be performed along 60% of the coast without losing accuracy.